Size‐ and Halide‐Dependent Auger Recombination in Lead Halide Perovskite Nanocrystals - Li, Yulu; Luo, Xiao; Ding, Tao; Lu, Xin; Wu, Kaifeng (Angewandte Chemie International Edition, 2020)
Lead halide perovskite nanocrystals (NCs) hold strong promise for a variety of light‐harvesting, emitting, and detecting applications, all of which, however, could be complicated by multicarrier Auger recombination. Therefore, complete documentation of the size‐ and composition‐dependent Auger recombination rates of these NCs is highly desirable, as it can guide system design in many applications. Herein we report the synthesis and Auger measurements of monodisperse APbX3 (A=Cs and FA; X=Cl, Br, and I) NCs in an extensive size range (ca. 3–9 nm). The biexciton Auger lifetime of all the NCs scales linearly with the NC volume. The scaling coefficient is virtually independent of the cation but rather depends sensitively on the anion, and is 0.035, 0.085, and 0.142 ps nm−3 for Cl, Br, and I, respectively. In all of these nanocrystals the Auger recombination is much faster than in standard CdSe and PbSe NCs (ca. 1 ps nm−3). Lawful behavior: A wide range of monodisperse lead perovskite nanocrystals with different cation and anion compositions and varying sizes were synthesized and their biexciton Auger recombination lifetimes measured by ultrafast spectroscopy (see picture). Volume scaling laws for the Auger lifetime of the nanocrystals were determined, thus enabling facile estimation of Auger rates, which are key parameters for perovskite‐nanocrystal‐based devices.